Knot Security of 5 Metric (USP 2) Sutures: Influence of Knotting Technique, Suture Material, and Incubation Time for 14 and 28 Days in Phosphate Buffered Saline and Inflamed Equine Peritoneal Fluid. Issue 6 (22nd May 2015) - Sanders, Ruth E.; Kearney, Clodagh M.; Buckley, Conor T.; Jenner, Florien; Brama, Pieter A
Abstract : Objectives: To evaluate knot security for 3 knot types created in 3 commonly used 5 metric suture materials incubated in physiological and pathological fluids. Study Design: In vitro mechanical study. Sample Population: Knotted suture loops (n = 5/group). Methods: Loops of 3 different suture materials (glycolide/lactide copolymer; polyglactin 910; polydioxanone) were created around a 20 mm rod using 3 knot types (square [SQ], surgeon's [SK], and triple knot [TK]) and were tested to failure in distraction (6 mm/min) after tying (day 0) and after being incubated for 14 and 28 days in phosphate buffered saline (PBS) or inflamed peritoneal fluid. Failure load (N) and mode were recorded and compared. Results: For polydioxanone, significant differences in force to knot failure were found between SQ and SK/TK but not between SK and TK. The force required to break all constructs increased after incubation in phosphate buffered saline (PBS). With glycolide/lactide copolymer no differences in force to knot failure were observed. With polyglactin 910, a significant difference between SQ and TK was observed, which was not seen between the other knot types. Incubation in inflamed peritoneal fluid caused a larger and more rapid decrease in force required to cause knot failure than incubation in PBS. Conclusions: Mechanical properties of suture materials have significant effects on knot security. For polydioxanone, SQ is insufficient to create a secure knot. Additional wraps above a SK confer extra stability in some materials, but this increase may not be clinically relevant or justifiable. Glycolide/lactide copolymer had excellent knot security.